STRATEGI DINAS KESEHATAN KABUPATEN SUMENEP DALAM GERAKAN VAKSINASI COVID-19 - Amin Fajar shadiq; M. Mas’ud Said; Hayat Hayat (Universitas Islam Darul Ulum Lamongan, 2021)
The purpose of this study is to discuss the Sumenep District Health Service Strategy in the Covid-19 Vaccination movement. In this study, of course, focusing on the strategy realized by the Sumenep District Health Office in the Covid-19 Vaccination Movement, of course this strategy aims to create a successful Vaccination Movement in Sumenep Regency. the community and community groups to carry out the Covid-19 Vaccination, in implementing the Covid-19 Vaccination Movement Strategies, the Sumenep District Health Office cooperates with all aspects of the Sumenep Regency Government, the TNI. Police, sub-district heads, village heads, religious leaders and the community. In practice, the Covid-19 Vaccination Movement certainly faces many obstacles, but the obstacles faced are not only the rejection by the community or community groups, the obstacles are also caused by geographical factors that do not support it so that the existence of these obstacles will certainly have an impact. Therefore, with the implementation of good strategies and innovations from the Sumenep District Health Office, the Covid-19 Vaccination Movement can be said to be good and successful in achieving the specified target. We use a descriptive method with a qualitative approach where researchers use information sources in the field to find information as deep as possible.